2011
DOI: 10.5251/abjna.2011.2.5.806.817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot water treatment on quality and shelf-life of Keitt mango

Abstract: Mango anthracnose, a major postharvest disease, induces huge losses in mangoes and threatens mango export and consumption. The effectiveness of hot water treatment as a postharvest disease control measure on Keitt cultivar of mango was assessed over a 21-day storage period. Batches of fruits were subjected to various degrees of hot-water treatments at temperatures proved to be effective in controlling anthracnose disease on Keitt fruits after 7 days in storage, whereas the control showed the highest incidence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
2
11
1
1
Order By: Relevance
“…Reports on both hot water and calcium chloride on the Keitt mango fruits pH are scarce but the reference [41] assessing the effect of hot water treatment on quality and shelf-life of Keitt mango reported increasing trend in the pH values while the hot water temperature and the processing time were increasing, contrasting with this work where the optimum point is know.…”
Section: Models and Surface Predicted Responsescontrasting
confidence: 53%
“…Reports on both hot water and calcium chloride on the Keitt mango fruits pH are scarce but the reference [41] assessing the effect of hot water treatment on quality and shelf-life of Keitt mango reported increasing trend in the pH values while the hot water temperature and the processing time were increasing, contrasting with this work where the optimum point is know.…”
Section: Models and Surface Predicted Responsescontrasting
confidence: 53%
“…This treatment reduces the incidence of anthracnose and stem-end rot by 10%, resulting in almost a 100% recovery rate and an increase in sales and income (Aveno and Excelsis, 2010). Kumah et al (2011) reported that hot water treatment at 52°C for 5 min was the best treatment for controlling anthracnose in Keitt mangoes during 21 days of storage. Thermal treatment is suitable for tropical fruits because tropical fruits tolerate heat well (Mansour et al, 2006).…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…Mango is a climacteric fruit and has quite a long shelf life of more than 10 days if not attacked by fungi (Siriphanich, 2002). The two most serious fungal diseases of tropical and subtropical fruits such as mango, banana, papaya, and avocado are powdery mildew (Oidium mangiferae) and anthracnose (Colletotrichum gloeosporioides), which are prevalent in regions with high humidity (Kumah et al, 2011). Approximately 20~25% of the harvested fruits and vegetables decay because of pathogens during postharvest handling even in developed countries (Zhu, 2006).…”
Section: Microbial Contamination and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…According Olivero-Verbel et al (2010) and Utta-U´r et al (2000) inhibitory effect of cardamom essential oil on fungi maybe due to 1,8-cineol (29.7%) and α-terpineol acetate (26.1%) the main components found in the volatile oil. Hot water treatment is known to be an effective and environmental-friendly method for controlling postharvest diseases of mango (Kumah et al, 2011;Duamkhanmanee, 2008). Therefore, in the present study the EO with fungicidal components and the hot water treatment which can also control post-harvest diseases would have in combination brought about the significant reduction in SER in treated mango fruits.…”
Section: Sensory Evaluation Of Fruits Treated With Essential Oilsmentioning
confidence: 80%